Corruption and foreign direct investment inflows: Evidence from West Africa - William Bekoe; Talatu Jalloh; Wassiuw Abdul Rahaman (International Journal of Business and Economic Sciences Applied Research (IJBESAR), 2021)
Purpose: The study investigates the effect of corruption on FDI inflows to West Africa, and also establishes a threshold level of corruption for the sub-region. Design/Methodology/Approach: Using secondary data for the period 1999-2018, the study adopted a panel Autoregressive Distributed Lag (ARDL) model to carry out regression analysis. However, to ensure results accuracy and validity, a cross section dependence test, panel unit root test and panel cointegration test was carried out. Findings: The results indicated that in the long-run, corruption adversely affects the inflow of FDI to West Africa, thus lending support to the grabbing hand hypothesis. The study found the long-run threshold level of corruption for West Africa to be 6.3, indicating that below this level FDI inflow cannot be discouraged by corruption otherwise, FDI inflows could be discouraged. Research limitations/Implications: The findings from the study suggests that governments from West Africa should focus on mechanisms that will strongly discourage people from engaging in corruption, such as reducing the delays in business registration, strengthening and ensuring of effective monitoring of public institutions, as well as introducing the practice of penalty and exhortation in the public sector. Quality/Value: The present study contributes to the literature by investigating the effects of corruption on the inflow of FDI to West Africa using a more appropriate macro panel estimation technique, the panel Autoregressive Distributive Lag (ARDL) technique. Furthermore, it provides a threshold level for corruption on FDI inflows in West Africa.
Keywords: H6; H63; H68; 330; Foreign Direct Investment; Corruption; Corruption Threshold; West Africa; Panel Autoregressive Distributed Lag (ARDL) Model